Critical reading ability and its relation to L2 proficiency of Malaysian ESL learners - Zuhana Mohd Zin,; Wong, Bee Eng; Shameem Rafik-Galea, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
Critical reading is an important ability to acquire particularly among college or university students. This study investigated the level of critical reading skills among Malaysian ESL learners at the tertiary level. The motivation for conducting the study is due to the increasing number of claims by employers and educators that most graduates lack the ability to read and think critically. Among the required reading and thinking abilities necessary to read a text critically are the analytical and inference skills. Specifically, this study examined the ESL learners’ analytical and inference skills when they read two expository texts. A self-developed critical reading comprehension test (CRCT) was used to measure their analytical skills in identifying the writer’s purpose and the main ideas in the text. The findings indicated that the students lacked the required critical skills, in particular, when they are required to identify the writer’s purpose and the main idea in the text which support the observation and experience of many Malaysian educators and researchers. This has direct implications on reading development in Malaysia.